2007
DOI: 10.2478/v10012-007-0040-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental research on effectiveness of the magnetic fluid seals for rotary shafts working in water

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 5 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…They found that when the shaft diameter was large, the gravity should be considered, and the centrifugal force had an influence on the MFS capacity. Szydło and Matuszewski [119] carried out the tests for specially selected profiles of sealing lips and hydrophobic magnetic fluids at various linear velocities in a sealing unit. Although the tests were preliminary, their results showed that the studies about applications of MFSs working in liquid environment should continue.…”
Section: Magnetic Fluid Rotary Sealingmentioning
confidence: 99%
“…They found that when the shaft diameter was large, the gravity should be considered, and the centrifugal force had an influence on the MFS capacity. Szydło and Matuszewski [119] carried out the tests for specially selected profiles of sealing lips and hydrophobic magnetic fluids at various linear velocities in a sealing unit. Although the tests were preliminary, their results showed that the studies about applications of MFSs working in liquid environment should continue.…”
Section: Magnetic Fluid Rotary Sealingmentioning
confidence: 99%
“…Some years earlier in AGH Laboratory, the tests of MFseals operating in utility water environment were carried out [12,13,14] in order to assess their applicability in shipbuilding. Results of the tests conducted in the years 2009÷2010 on the test stand adjusted to operation of the seals in liquids [15] showed that it is possible to apply some commercial magnetic fluids to MF seals operating in direct contact with water in working conditions which occur in many devices met not only in ocean engineering.…”
Section: Gdansk University Of Technology Polandmentioning
confidence: 99%
“…As a new type of functional material, magnetic fluid has unique properties with both superparamagnetism and fluidity [1,2], which can be controlled by the action of an external magnetic field [3,4]. The magnetic fluid sealing technology is an excellent sealing technique and has been mature for gas sealing, but it is still in the early stage of sealing water [5].…”
Section: Introductionmentioning
confidence: 99%